Pengaruh Lama Penyimpanan dan Konsentrasi Aplikasi Ekstrak Biji Mahoni Hasil Fermentasi terhadap Efektivitasnya - Hamdani Hamdani; Dedi Supriyatdi (Jurnal Agro Industri Perkebunan, 2017)
Armyworm (Spodoptera litura F.) as a polyfagous insect is a key pest of either food crops or estate crops. The larva often attack leaves of beans, cereal, shallot, cabbage, cotton, tobacco, and sugarcane. Synthetic insecticides are usually used 2 – 3 times a week in order to manage this insect. The use of synthetic insecticides need high cost, have negative impacts such as insect resistance and resurgence, killing non-target insects, residual effects on yield, and environmental contamination and pollution. Botanical insecticide has a highly potential to be used in IPM because of its characteristics (no residual effect, cheap, easy to get and easy to apply). Mahogany seeds contain alkaloid, saponin, and flavonoid that have good insecticide activity. Extract of mahogany seeds can be used as insecticide, anti-feedant, growth retardant, and fertile retardant. The effectivity of mahogany seed extracts is affected by storage time and its concentration. The results of the experiment are the extract of mahogany seeds can be stored up to 3 weeks, and the highest effective is reached by the concentration of 20%, followed by 10% - 15% concentration as moderately effective.   Keywords: botanical insecticides, extract, mahogany seedPermalink: http://jurnal.polinela.ac.id/index.php/AIP/article/view/652